Sorption of heavy metals using low cost sorbents: alternative method for water treatment - Kamari Azlan, Md Isa Illvas, Hashim Norhayati (Universiti Pendidikan Sultan Idris, 2013)
Sorption of heavy metals using low cost sorbents: alternative method for water treatment by Kamari Azlan, Md Isa Illvas, Hashim Norhayati,